Keprofesionalan Konseling dan Psikoterapin Ditinjau dari Konsep Serta Prosesnya: Array - Athalia A. Aptanta Tumanggor; Mujiran; Dina Sukma (eductum: Jurnal Literasi Pendidikan, 2023)
Professional services that humans can use nowadays are counseling and psychotherapy services. Both services can help people prevent or overcome obstacles and problems that occur in their lives that disrupt practical daily life. One of the obstacles or problems that humans often face in achieving an effective life is psychological disorders. Basically, counseling and psychotherapy are assistance services that have the same goal but in concept, there are slight differences. This research method uses literature studies, the purpose of this research is to explore and examine counseling and psychotherapy in terms of concepts and processes. This research uses a number of data, including books, research reports, and scientific articles.